Utility of Red Tide (Karenia brevis) Monitoring Data as a Predictive Tool to Estimate Brevetoxin Accumulation in Live, Free-Ranging Marine Mammals - Fire, Spencer E.; Miller, Glenn A.; Sabater, Edna R.; Wells, Randall S. (Frontiers in Marine Science, 2021)
Exposure of common bottlenose dolphins (Tursiops truncatus) to brevetoxins (PbTx) produced by Karenia brevis blooms frequently results in large-scale mortality events, but data on relationships between bloom severity and corresponding PbTx concentrations in exposed live animals are lacking. Here we present results of PbTx analysis of samples from live, free-ranging dolphins (n=253) from Sarasota Bay, Florida during 2000-2018, and investigate the relationship between PbTx concentrations detected and corresponding K. brevis cell abundances associated with each individual. 28% of dolphins were associated with elevated K. brevis abundances (>10,000 cells/L), and 41% (n=104) of dolphins were PbTx-positive. The proportion of PbTx-positive animals was significantly greater in animals exposed to elevated cell abundances vs. those exposed to background cell abundances (<10,000 cells/L), with 60% and 34% testing positive, respectively. PbTx was detected most frequently in feces (57%), followed by gastric (35%), urine (32%), and blood (7%). PbTx concentrations were highest in feces (2-231 ng/g; mean 46), followed by urine (0.8-90 ng/g; mean 7.2), gastric (0.8-61 ng/g; mean 12), and blood (0.3-5 ng/g; mean 1.3). Analyses of K. brevis cell abundance as an index of exposure vs. corresponding PbTx concentration found no statistically significant relationship for feces, gastric, urine, or blood samples. PbTx concentrations typically did not scale with corresponding indices of exposure. Our results indicate that K. brevis cell abundance alone is a poor predictor of brevetoxin accumulation in bottlenose dolphins, and alternative biomarkers should be investigated as more appropriate methods for determining the severity of health impacts due to red tides.